Heatwaves as an occupational hazard: The impact of heat and heatwaves on workers' health, safety and wellbeing and on social inequalities - Claudia Narocki (European Trade Union Institute (ETUI), 2021)
Weather-related heat exposure has become a sanitary concern given the wide repercussions it has for health. Both physiological and epidemiological research show that the impact of heat on human health goes far beyond acute heat conditions such as potentially fatal heat strokes. Heat exacerbates the problems associated with a wide variety of cardiovascular, respiratory and other acute illnesses and reproductive health. During heatwaves there is an increase in injury-related mortality in comparison with that experienced in communities' usual climates; a part of this is occupationally-related. Such events add risks in particular to working people, especially when these are topped by pre-existing occupational heat stress factors, as the use of personal protective equipment, which can hinder the dissipation of body heat, exertion or other occupational hazards. As climate change is multiplying the number of hot days and their intensity, and adding to the period of summer, a greater variety of occupations are becoming potentially exposed to heat. Some jobs have become exposed as a result of the 'non stop' economy and the contemporary management of working time. We argue here that weather-related heat stress should be considered an escalating occupational hazard that deserves full societal recognition in order to be considered as an emerging occupational risk requiring public action.
Keywords: 330; Weather; health risk; Working conditions; employee protection; Wetter; Gesundheitsrisiko; Arbeitsbedingungen; Arbeitnehmerschutz